Formation of a new visually of cities in the XXI century: architectural strategies of Asian countries - Konovalova, N. A.; Maevskaya, M. E. (Sot͡s︡iologii͡a︡ goroda, 2025)
The research was carried out at the expense of the state program of fundamental scientific research of the Russian Federation for the long-term period (2021—2030) within the framework of the Plan of Fundamental Scientific Research of the Russian Academy of Sciences and the Ministry of Construction of Russia for 2023. Over the past two decades, there has been a qualitative leap in the intensification of urban development in China, India, South Korea, Indonesia and other countries of the Asian region, as well as in the Middle East. This process has affected both existing cities with deep historical roots and completely new urban formations. Numerous planning and construction of new cities, reformatting of space and intensive development of historical settlement sites have developed a certain series of strategies that have received their pronounced regional specificity. This article is devoted to the identification and analysis of the tools of these regional strategies of urban development in the modern world